2004
DOI: 10.1074/jbc.m305526200
|View full text |Cite
|
Sign up to set email alerts
|

Merlin Neutralizes the Inhibitory Effect of Mdm2 on p53

Abstract: The stability of p53 tumor suppressor is regulated by Mdm2 via the ubiquitination and proteasome-mediated proteolysis pathway. The c-Abl and PTEN tumor suppressors are known to stabilize p53 by blocking the Mdm2-mediated p53 degradation. This study investigated the correlation between p53 and merlin, a neurofibromatosis 2 (NF2)-related tumor suppressor, in association with the Mdm2 function. The results showed that merlin increased the p53 stability by inhibiting the Mdm2-mediated degradation of p53, which acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
45
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 38 publications
3
45
1
Order By: Relevance
“…In addition, recent studies have suggested a role for NF2 in the inhibition of the p53 regulatory protein, Mdm2, whereby NF2 promotes degradation of Mdm2, thus stabilizing p53. Such findings parallel those described in our mouse model and suggest potential functional consequences for NF2 interaction with Tantigen and/or p53 (Kim et al, 2004). One may envision a scenario in which T-antigen may bind to p53 and/or NF2, thus inactivating the G1/S checkpoint and possibly other cell cycle regulatory pathways downstream of NF2.…”
Section: Discussionsupporting
confidence: 62%
“…In addition, recent studies have suggested a role for NF2 in the inhibition of the p53 regulatory protein, Mdm2, whereby NF2 promotes degradation of Mdm2, thus stabilizing p53. Such findings parallel those described in our mouse model and suggest potential functional consequences for NF2 interaction with Tantigen and/or p53 (Kim et al, 2004). One may envision a scenario in which T-antigen may bind to p53 and/or NF2, thus inactivating the G1/S checkpoint and possibly other cell cycle regulatory pathways downstream of NF2.…”
Section: Discussionsupporting
confidence: 62%
“…Moreover, we recently observed that merlin increased p53 activity by inducing MDM2 degradation in NIH3T3 cells (35). Considering all of these results and related papers, it would appear that merlin has multiple activities for tumor suppression, one of which might be the suppression of TRBP function reported herein.…”
Section: Discussionmentioning
confidence: 92%
“…Interestingly, promyelocytic leukemia regulates p53 stability by sequestering MDM2 to the nucleolus (57). Similarly, merlin (neurofibromatosis 2) increases the p53 stability by inhibiting the MDM2-mediated degradation of p53 (58). PTEN physically associates with endogenous p53 and regulates the transcriptional activity of p53 by modulating its DNA binding (59).…”
Section: Discussionmentioning
confidence: 99%